De autonomías y superposiciones. En torno a los usos de Bourdieu en la historiografía sobre intelectuales y política en la Argentina de los sesenta-setenta - Starcenbaum, Marcelo (2013)
The order you want to achieve in this work is to reconstruct the uses of Bourdieu's work on the historiography of intellectuals and politics in Argentina between 1960 and 1970. Through reading of the major works on this subject, we will analyze the place that occupied the Bourdieu's perspectives in formulating a model of intellectual sixties, politically engaged but with autonomous cultural interventions, and a model of the seventies, whose cultural creations were subordinated an absolute commitment to the policy
O fim que se quer atingir neste trabalho é reconstruir os usos da obra de Bourdieu sobrea historiografia dos intelectuais e da política na Argentina entre 1960 e 1970. Através daleitura das principais obras sobre este assunto, vamos analisar o lugar que ocupava aperspectiva bourdiana na formulação de um modelo de intelectual dos anos sessenta,politicamente engajado mas com intervenções culturais autônomas, e um modelo dosanos setenta, cujas criações culturais estavam subordinadas a um compromisso absolutocom a política
Keywords: Intelectuales; Bourdieu; Argentina; Intelectuals; Bourdieu; Argentina; 1960; 1970; Intelectuais; Bourdieu; Argentina; 1960; 1970^lpt